Pengaruh Motivasi, Komitmen Organisasi, dan Kompetensi Pedagogik Terhadap Kinerja Guru Sekolah Dasar : Studi Kasus Anggota Kelompok Kerja Guru (KKG) Kecamatan Teluk Sebong (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study aims to analyze the influence of motivation, organizational commitment, and pedagogical competence on the performance of elementary school teachers who are members of the Teacher Working Group (KKG) in Teluk Sebong District. The research employed a quantitative approach with a saturated sampling technique, involving all 112 teachers as respondents. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression through SPSS software. The partial test results show that motivation has a positive and significant effect on teachers' performance (t = 3.768; sig = 0.000), organizational commitment has a positive and significant effect on teachers' performance (t = 2.093; sig = 0.039), and pedagogical competence has a positive and significant effect on teachers' performance (t = 3.059; sig = 0.003). Simultaneously, the three variables significantly affect teachers' performance (F = 9.153; sig = 0.000). The determination coefficient indicates an R Square value of 0.203, meaning that 20.3% of the variation in teachers' performance can be explained by motivation, organizational commitment, and pedagogical competence, while the remaining 79.7% is influenced by other factors outside this model.